DEVELOPMENT OF TEACHING MATERIALS ALGEBRAIC EQUATION TO IMPROVE PROBLEM SOLVING - sri adi widodo (IKIP Siliwangi and I-MES, 2017)
Problem-solving skills are the basic capabilities of a person in solving a problem and that involve critical thinking, logical, and systematic. To solve a problem one-way necessary measures to solve the problem. Polya is one way to solve a mathematical problem. by developing teaching materials designed using the steps in solving problems Polya expected students could improve its ability to solve problems. In this first year, the goal of this study is to investigate the process of learning the hypothetical development of teaching materials. This study is a research & development. Procedure development research refers to research the development of Thiagarajan, Semmel & Semmel ie 4-D. Model development in the first year is define, design, and development. The collection of data for the assessment of teaching materials algebra equations conducted by the expert by filling the validation sheet. Having examined the materials of algebraic equations in the subject of numerical methods, reviewing the curriculum that is aligned with KKNI, and formulates learning outcomes that formed the conceptual teaching material on the material algebraic equations. From the results of expert assessment team found that the average ratings of teaching materials in general algebraic equation of 4.38 with a very good category. The limited test needs to be done to see effectiveness teaching materials on problem-solving skills in students who are taking courses numerical methods